2014
DOI: 10.1063/1.4873406
|View full text |Cite
|
Sign up to set email alerts
|

Indirect-direct band gap transition through electric tuning in bilayer MoS2

Abstract: We investigate the electronic properties of bilayer MoS2 exposed to an external electric field by using first-principles calculations. It is found that a larger interlayer distance, referring to that by standard density functional theory (DFT) with respect to that by DFT with empirical dispersion corrections, makes indirect-direct band gap transition possible by electric control. We show that external electric field effectively manipulates the valence band contrast between the K- and Γ-valleys by forming built… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…5c and 5d. Similar phenomenon was clarified in our previous work [45]. It was demonstrated that the symmetry of the built-in electric dipole field controlled the indirect-direct bandgap transition in bilayer MoS 2 subjected to external electric fields.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…5c and 5d. Similar phenomenon was clarified in our previous work [45]. It was demonstrated that the symmetry of the built-in electric dipole field controlled the indirect-direct bandgap transition in bilayer MoS 2 subjected to external electric fields.…”
Section: Resultsmentioning
confidence: 53%
“…2a. While for the c-12 with external electric fields increasing, the bandgap width decreases until it finally closes due to the well known Stark effect [44,45]. In addition, before the bandgap closes at ∼0.71 eV/Å (see Fig.…”
Section: Resultsmentioning
confidence: 91%
“…The behaviour of bilayer MoS 2 in a layer perpendicular electric field has been well established by DFT studies: the band gap can be continuously reduced with increasing field strength5232425. This tuning of the band gap is so dramatic that both (i) a transition from indirect to direct band gap and (ii) full metalization can be observed (at 1–2 V/nm and 2–3 V/nm respectively, depending on the stacking type of the bilayer).…”
Section: Resultsmentioning
confidence: 92%
“…Also, it would be of great interest for valleytronic applications via achieving degenerate energy valleys at different k-points. [21][22][23][24] Second, the indirect-direct bandgap transition observed in arsenene nanoribbons provides researchers with solid evidence to engineer the bandgap properties of similarly puckered structures or other non-planar structures. Future experiments can test our proposal directly.…”
Section: Electronic Structures Of Zanrsmentioning
confidence: 99%